The effect of hip abductor fatigue on knee kinematics and kinetics during normal gait - Tang, Yuting; Li, Yanfeng; Yang, Maosha; Zheng, Xiao; An, Bingchen; Zheng, Jiejiao (Frontiers in Neuroscience, 2022)
Objective: To investigate the effect of hip abductor fatigue on the kinematics and kinetics of the knee joint during walking in healthy people to provide a new approach for the prevention and treatment of knee-related injuries and diseases. Methods: Twenty healthy participants, ten females and ten males, with a mean age of 25.10 ± 1.2 yr, were recruited. Isometric muscle strength testing equipment was used to measure the changes in muscle strength before and after fatigue, and the surface electromyography (SEMG) data during fatigue were recorded synchronously. The Vicon system and an AMTI© force platform were used to record the kinematic parameters and ground reaction force (GRF) of twenty participants walking at a self-selected speed before and after fatigue. Visual 3D software was used to calculate the angles and torques of the hip and knee joints. Results: After fatigue, the muscle strength, median frequency (MF) and mean frequency (MNF) of participants decreased significantly (P < 0.001). The sagittal plane range of motion (ROM) of the knee (P < 0.0001) and hip joint (P < 0.01) on the fatigue side was significantly smaller than before fatigue. After fatigue, the first and second peaks of the external knee adduction moment (EKAM) in participants were greater than before fatigue (P < 0.0001), and the peak values of the knee abduction moment were also higher than those before fatigue (P < 0.05). On the horizontal plane, there is also a larger peak of internal moment during walking after fatigue (P < 0.01). Conclusion: Hip abductor fatigue affects knee kinematics and kinetics during normal gait. Therefore, evaluating hip abductor strength and providing intensive training for patients with muscle weakness may be an important part of preventing knee-related injuries.